Anti-programmed cell death protein 1 tolerance and efficacy after ipilimumab immunotherapy: observational study of 39 patients. Issue 2 (April 2017) - Amode, Reyhan; Baroudjian, Barouyr; Kowal, Anita; Jebali, Majdi; Allayous, Clara; Bagot, Martine; Madjlessi, Nika; Roux, Jennifer; Viguier, Manuelle; Basset Seguin, Nicole; Porcher, Raphaël; Pagès, Cécile; et al.
Abstract : In patients with ipilimumab (IPI)-refractory melanoma, the anti-programmed cell death proteins 1 (PD1s) nivolumab (NIV) and pembrolizumab (PEM) are considered to be a new standard of treatment. Few data are available on anti-PD1 safety in patients who develop IPI-related severe adverse events (AEs) (grade≥3). The aim of this study was to compare the anti-PD1 safety and efficacy in patients with previous severe toxicity to IPI versus in those showing moderate and no previous IPI-related AEs. This single institution-based observational study included all patients treated with anti-PD1 (PEM or NIV) and previously treated with IPI for unresectable stage III or IV melanoma. The patients enrolled were classified according to the occurrence of IPI-related AEs: group A: no previous IPI-related AEs; group B: mild to moderate IPI-related AEs; and group C: severe to life-threatening IPI-related AEs. The main outcome measure was safety of the anti-PD1 among the three groups. The secondary endpoints included response parameters. Groups A, B, and C included, respectively, 16, 13, and 10 patients. The incidence of severe anti-PD1-related AEs (grades 3–4) was 12, 23, and 10% in groups A, B, and C, respectively. One-year estimates of survival were 52.2, 73.4, and 66.7% among the patients in groups A, B, and C, respectively. The number of patients was too small to enable a meaningful statistical comparison. We did not observe any difference in anti-PD1 toxicity onset incidence according to the occurrence of previous IPI AEs. These reassuring real-life data should be confirmed in a wider analysis.